The Semiotic Meaning and Philosophy of Symbols in the Gayo Ethnic Marriage Processions in Central Aceh - Auni, Luthfi; Nidawati, Nidawati (Jurnal Ilmiah Peuradeun, 2023)
This research critically studied the verbal and nonverbal symbols in the processions of the marriage tradition of the Gayo ethnic in Central Aceh by tracing back, exploring and examining all symbols and their symbolic meanings and philosophy as an effort of preserving one of the Gayo traditional heritages. Its main aim was to describe unique verbal and non-verbal symbolic features with semiotic meanings and philosophical messages based on the local values of the Gayo ethnic. The study employed a qualitative research design. The data were collected from observation, interviews and documentation. The data were analyzed with the Miles and Huberman interactive models consisting of data reduction, data display, and conclusion drawing/ verification. Meanwhile result analysis was based on the semiotic analysis of Roland Barthes. The result showed that most of the series of phases of Gayo ethnic marriage processions were filled with verbal and non-verbal symbols, which have semiotic meanings and philosophical messages which are still used until this day. However, many of those verbal and nonverbal symbols have no longer been understood well by Gayo young generation. Consequently, they only perform the series of processions as a formality without understanding the meaning of each symbol.